Digital Simulation and Experimental Validation of Redox Mediation at an Electroactive Monolayer-Coated Electrode. Issue 4 (2nd March 2020) - Mayall, Robert M.; Birss, Viola I.; Creager, Stephen E.
Abstract : A commercial digital simulation tool was used to simulate cyclic voltammetry (CV) data for redox mediation electrode reactions involving immobilized redox mediators. The system studied consists of a ferrocene-based redox mediator in an alkanethiolate-based self-assembled monolayer (SAM) on gold, with ferrocyanide in solution acting as electron donor to react with electrogenerated ferrocenium in the monolayer. Simulation parameters include rate constants for ferrocene oxidation/reduction in the monolayer, the mediation cross reaction between ferrocenium in the monolayer and ferrocyanide in solution, and the direct (unmediated) ferrocyanide oxidation/reduction reaction by long-range electron transfer across the monolayer. An excellent agreement between simulation and experiment was obtained using simulation parameters derived from independent experiments. The simulation method enables analysis of an entire voltammogram which can offer advantages over analytical approaches that consider only a portion of the data (e.g., a "foot-of-the-wave" analysis). The availability of a validated simulation tool allows questions about the anticipated reactivity of immobilized redox mediators to be addressed definitively via simulation, rather than by speculation on the effects one might expect to observe on a CV waveshape for a particular parameter change.